Diet composition and the performance of high-intensity exercise - Maughan, R. J.; Greenhaff, P. L.; Leiper, J. B.; Ball, D.; Lambert, C. P.; Gleeson, M. (Journal of Sports Sciences, 1997)
The crucial role of muscle glycogen as a fuel during prolonged exercise is well established, and the effects of acute changes in dietary carbohydrate intake on muscle glycogen content and on endurance capacity are equally well known. More recently, it has been recognized that diet can also affect the performance of high-intensity exercise of short (2-7 min) duration. If the muscle glycogen content is lowered by prolonged (1-1.5 h) exhausting cycle exercise, and is subsequently kept low for 3-4 days by consumption of a diet deficient in carbohydrate (<5% of total energy intake), there is a dramatic (~10-30%) reduction in exercise capacity during cycling sustainable for about 5 min. The same effectis observed if exercise is preceded by 3-4 days on a carbohydrate-restricted diet or by a 24 h total fast without prior depletion of the muscle glycogen. Consumption of a diet high in carbohydrate (70% of total energy intake from carbohydrate) for 3-4 days before exercise improves exercise capacity during high-intensity exercise, although this effect is less consistent. The blood lactate concentration is always lower at the point of fatigue after a diet low in carbohydrate and higher after a diet high in carbohydrate than after a normal diet. Even when the duration of the exercise task is kept constant, the blood lactate concentration is higher after exercise on a diet high in carbohydrate than on a diet low in carbohydrate. Consumption of a low-carbohydrate isoenergetic diet is achieved by an increased intake of protein and fat. A high-protein diet, particularly when combined with a low carbohydrate intake, results in metabolic acidosis, which ensues within 24 h and persists for at least 4 days. This appears to be the result of an increase in the circulating concentrations of strong organic acids, particularly free fatty acids and 3-hydroxybutyrate, together with an increase in the total plasma protein concentration. This acidosis, rather than any decrease in the muscle glycogen content, may be responsible for the reduced exercise capacity in high-intensity exercise; this may be due to a reduced rate of efflux of lactate and hydrogen ions from the working muscles. Alternatively, the accumulation of acetyl groups in the carbohydrate-deprived state may reduce substrate flux through the pyruvate dehydrogenase complex, thus reducing aerobic energy supplyand accelerating the onset of fatigue.